Fatalities due to methyl alcohol intoxication in Turkey: an 8-year study - (:unkn) unknown (ELSEVIER IRELAND LTD, 2003)
The aim of this study is to examine methyl alcohol poisoning cases from the medico-legal point of view. The records of the Morgue Department of Council of the Forensic Medicine were reviewed retrospectively for all methyl alcohol poisonings for the period of 27.10.1992 and 30.05.2001. The victim's age, sex, death year, death place, methyl alcohol blood levels, the source of methyl alcohol, accompanying laboratory results and histopathologic tissue changes were recorded. The number of deaths due to the methyl alcohol poisoning was 271 during that period of time. Two hundred and forty-two of the (89.3%) total 271 methyl alcohol fatalities were men and 29 (10.7%) of were women. The largest age group was 36-40 years old, followed by 41-45. The methyl alcohol blood concentrations ranged widely from 50 to 755 mg for per 100 ml. There were 222 cases (81.9%) with the methyl alcohol blood concentrations over 100 mg/dl. Twenty-nine (10.7%) victims were poisoned through the consumption of cologne and three of them with alcoholic beverage named Raki. Consumed products were not known in all other cases because of insufficient patient history and data. As a conclusion, regarding the distribution according to years, mortality due to methyl alcohol intoxication in our country have been proceeding on a certain level. In order to decrease the mortality due to methyl alcohol intoxication, some precautions should be developed that could prevent the production and consumption of alcoholic beverages illegally produced. (C) 2003 Published by Elsevier Science Ireland Ltd.
Keywords: methyl alcohol; fatalities; intoxication; METHANOL INTOXICATION; OCULAR TOXICITY; FORMATE